Mothers' Perspectives of Complementary Feeding Practices in an Urban Informal Settlement in Kisumu County, Western Kenya. Issue 5 (14th April 2021) - Reynolds, Elise C; Onyango, Dickens; Mwando, Rael; Oele, Elizabeth; Misore, Thomas; Agaya, Janet; Otieno, Peter; Tippett Barr, Beth A; Lee, Gwenyth O; Akelo, Victor
ABSTRACT: Background: In informal settlements, the benefits of urban dwelling are diminished by conditions of poverty that exacerbate child undernutrition. The Child Health and Mortality Prevention Surveillance (CHAMPS) project has identified malnutrition as the leading underlying cause of death in children under 5 in the Manyatta urban informal settlement in Kisumu County, Kenya. Objective: This qualitative study, nested within the CHAMPS project, aimed to understand community perspectives on complementary feeding practices in this settlement. Methods: In-depth interviews were conducted with 20 mothers who lived in the urban informal settlement and had a child 6–23 months old. Two focus group discussions were conducted, 1 with mothers and 1 with community health workers (CHWs), to further explore themes related to complementary feeding. Results: Mothers were knowledgeable about globally recommended feeding practices, but such practices were often not implemented due to 1 ) the community/household water and sanitation environment, 2 ) the community/household food environment, 3 ) a lack of income and employment opportunities for women, and 4 ) sociocultural factors. Together, these create an environment that is not conducive to optimal child feeding practices. Conclusions: To improve complementary feeding practices and child nutritional outcomes in Kenya's informal urban settings, both community- and individual-level factors should be addressed. Possible interventions include investment in water infrastructure and social protection programs, such as cash transfers.